2015
DOI: 10.1371/journal.ppat.1005063
|View full text |Cite
|
Sign up to set email alerts
|

An In-Depth Comparison of Latency-Reversing Agent Combinations in Various In Vitro and Ex Vivo HIV-1 Latency Models Identified Bryostatin-1+JQ1 and Ingenol-B+JQ1 to Potently Reactivate Viral Gene Expression

Abstract: The persistence of latently infected cells in patients under combinatory antiretroviral therapy (cART) is a major hurdle to HIV-1 eradication. Strategies to purge these reservoirs are needed and activation of viral gene expression in latently infected cells is one promising strategy. Bromodomain and Extraterminal (BET) bromodomain inhibitors (BETi) are compounds able to reactivate latent proviruses in a positive transcription elongation factor b (P-TEFb)-dependent manner. In this study, we tested the reactivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
324
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 250 publications
(343 citation statements)
references
References 73 publications
15
324
3
1
Order By: Relevance
“…[78][79][80] It would seem that the combination of drugs provides a more effective reactivation and elimination of the persistently infected cells. 81,82 Nevertheless, a more achievable approach would be to better identify the main mechanism(s) causing viral latency, and improve our knowledge on the relative contribution of each of the silencing mechanisms involved. In this way, it will be feasible to target and eliminate the latent virus reservoir with the appropriated drug(s).…”
Section: Potential Therapeutic Treatment For Blv-infected Cowsmentioning
confidence: 99%
“…[78][79][80] It would seem that the combination of drugs provides a more effective reactivation and elimination of the persistently infected cells. 81,82 Nevertheless, a more achievable approach would be to better identify the main mechanism(s) causing viral latency, and improve our knowledge on the relative contribution of each of the silencing mechanisms involved. In this way, it will be feasible to target and eliminate the latent virus reservoir with the appropriated drug(s).…”
Section: Potential Therapeutic Treatment For Blv-infected Cowsmentioning
confidence: 99%
“…Combinations of PKC or MAPK agonists and LRAs will be needed to mitigate toxic effects and lower effective doses (73,74,91). Such LRAs include HDACis, BETis, and 5′ azacytidine, among others.…”
Section: Basic Mechanisms Of Hiv Latency and Reservoirmentioning
confidence: 99%
“…Such LRAs include HDACis, BETis, and 5′ azacytidine, among others. Indeed, vorinostat, romidepsin, panobinostat, and JQ1 act synergistically with PKC agonists to reactivate HIV transcription (43,(91)(92)(93)(94)(95). Whereas PKC agonists activate NF-κB and increase overall levels of P-TEFb and CycL/CDK11, LRAs primarily affect the P-TEFb equilibrium.…”
Section: Basic Mechanisms Of Hiv Latency and Reservoirmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the major problems in the search for effective LRAs is that, despite impressive activity in various in vitro models, most LRAs, including the HDAC inhibitors, have weak activity in ex vivo studies using resting CD4 + T cells from patients on ART (74). Fortunately, some combinations of LRAs are now beginning to show levels of latency reversal comparable to global T cell activation (75,76). In clinical trials, no reduction in the reservoir has yet been demonstrated, but there is evidence for increases in cell-associated HIV RNA and for slight transient increases in plasma HIV RNA with certain HDAC inhibitors (17,18).…”
Section: ) Infection Of Activated Cd4mentioning
confidence: 99%